Obese Patients Benefit, but do not Fare as Well as Nonobese Patients, Following Lumbar Spondylolisthesis Surgery: An Analysis of the Quality Outcomes Database. (16th November 2020) - Chan, Andrew K; Bisson, Erica F; Bydon, Mohamad; Glassman, Steven D; Foley, Kevin T; Potts, Eric A; Shaffrey, Christopher I; Shaffrey, Mark E; Coric, Domagoj; Knightly, John J; Park, Paul; Wang, Michael Y; et al.
Graphical Abstract: